The religious left and church-state relations - Shiffrin, Steven H., 1941- (Princeton University Press, 2009)
In The Religious Left and Church-State Relations, noted constitutional law scholar Steven Shiffrin argues that the religious left, not the secular left, is best equipped to lead the battle against the religious right on questions of church and state in America today. Explaining that the chosen rhetoric of secular liberals is poorly equipped to argue against religious conservatives, Shiffrin shows that all progressives, religious and secular, must appeal to broader values promoting religious liberty. He demonstrates that the separation of church and state serves to protect religions f.